Factors Influencing Muslims Compliance Behavior in Paying Zakah of Income: A Case Study in Jayapura (A Non-Muslim Region in Indonesia) - Ira Eka Pratiwi (P3M STAIN Kudus, 2018)
Indonesia is the forth largest population country and one of the most populous Muslims countries in the world. However, there are some regions in the eastern Indonesia that have small number of Muslims citizen, including Papua Province.  This research aims to examine the factors affecting Muslims’ compliance behavior in paying Zakah of income in Jayapura, a capital city of Papua Province, using Theory of Planned Behavior. Factors examined include attitude, subjective norm, perceived behavioral control and intention. This research used quantitative method with questionnaire as the instrument to collect the data. In this study, a total of 52 Muslims in Jayapura who had ever paid Zakah of income become the respondents. This research used multiple linear regressions to analyze the collected data with SPSS 19. After meeting the reliability and validity test, the result showed that subjective norm and perceived behavioral control significantly affected the Muslims’ intention in paying zakah of income, meanwhile attitude did not influence the Jayapura Muslims’ compliance behavior and it was affected significantly by their intention in paying Zakah of income and perceived behavior control. In general, the Theory of Planned Behavior can be used to determine Muslims’ compliance in paying Zakah.